2016
DOI: 10.1155/2016/1390345
|View full text |Cite
|
Sign up to set email alerts
|

Polyetherimide Nanofibres as Sorbents for Organochlorinated Pesticides Determination

Abstract: Electrospun polyetherimide (PEI) nanofibres were fixed on a steel wire solid phase microextraction (SPME) assembly. The basic properties of the prepared nanofibres were determined by thermogravimetry, differential scanning calorimetry, adsorption, and SEM. The analytical performance of prepared PEI SPME fibres was compared with three commercially available SPME fibres, 7 μm PDMS, 100 μm PDMS, and DVB/Carboxene/PDMS. As model water pollutants, persistent organochlorinated pesticides hexachlorocyclohexanes (HCH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Recent developments have seen chlorophenols (CPs) extensively used in the production of herbicides, fungicides, pesticides, insecticides, pharmaceuticals, and dyes [1][2][3] . Beyond these applications, CPs serve as preservative agents in the chemical industry for wood, paints, vegetable fibers, and leather, capitalizing on their potent antimicrobial properties [4][5][6] . Despite their utility, the adverse effects of CPs, including toxicity, carcinogenicity, teratogenicity, and mutagenicity 1,2,7 , cannot be overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments have seen chlorophenols (CPs) extensively used in the production of herbicides, fungicides, pesticides, insecticides, pharmaceuticals, and dyes [1][2][3] . Beyond these applications, CPs serve as preservative agents in the chemical industry for wood, paints, vegetable fibers, and leather, capitalizing on their potent antimicrobial properties [4][5][6] . Despite their utility, the adverse effects of CPs, including toxicity, carcinogenicity, teratogenicity, and mutagenicity 1,2,7 , cannot be overlooked.…”
Section: Introductionmentioning
confidence: 99%
“…Given the industrial and scientific importance of this polymer, studies have been reported, to our knowledge, for at least 13 years, especially concerning the use of PEI to produce fibers and mats by electrospinning [6][7][8][9][10][11][12][13][14]. For instance, Han et al [6] evaluated the thermal stability of electrospun mats formed by poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV)/PEI blends.…”
Section: Introductionmentioning
confidence: 99%
“…The PVA matrix, after being swelled with electrolyte solution, provided ion size (OH versus Zn OH 4 2-( ) ) dependent conductive pathways being this composite suitable for rechargeable zinc-air batteries. Vojtĕch et al [9] evaluated the electrospun polyetherimide (PEI) nanofibres in application as sorbents for organochlorinated pesticides (hexachlorocyclohexanes and chlorobenzene). The gas chromatography/mass spectroscopy (GCMS/MS) analyses showed better performance of electrospun PEI nanofibres than three commercial SPME fibers for representatives of organochlorinated pesticides.…”
Section: Introductionmentioning
confidence: 99%